Monitoramento Ubíquo de Veículos em Ambientes Urbanos: Um Estudo de Caso em Salvador com SDR e ADS-B - Coelho, José Ângelo Lefundes; Freitas, Allan Edgard Silva; Marques, Manoel Carvalho (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2025)
The growing demand for urban land mobility solutions has driven the development of vehicle tracking tools as a promising alternative for urban public transport in several parts of the world. A comprehensive literature review, using the Methodi Ordinatio, was carried out through a systematic search in electronic databases such as ScienceDirect, IEEE Xplore, Scopus, and Web of Science. Some articles were selected for a literature reviewthat addresses aspects of vehicle traceability applied in the context of public transport. We propose an approach based on SDR (Software Defined Radio) technology using ADS-B (Automatic Dependent Surveillance-Broadcast), the paper presents the results for a preliminary validation, considering a case study in the city of Salvador, Bahia.